Precise Synthesis at the Atomic Scale - Ji, Shufang; Jun, Caroline; Chen, Yuanjun; Wang, Dingsheng (Precision Chemistry, 2023)
Precise synthesis at the atomic scale is a highly desirable and controllable route for the preparation of heterogeneous catalysts with the desired structure and properties, which promotes the rational design of highly efficient catalysts and facilitates the understanding of structure-properties relationship. The precise construction of the active sites of the catalysts provides important opportunities for atomic insight into the correlation between structure and catalytic performance. In this review, the atomic-level tuning strategies for the precise synthesis of heterogeneous catalysts are summarized with the emphasis on the precise control of the structure of active sites, including single atom sites, dual atom sites and complex active sites. Furthermore, we illustrate the crucial role of atomic-level regulation of structure in determining the catalytic performance by providing typical catalysis examples in different reactions. In the end, some perspectives on the further development of precise synthesis of catalysts at the atomic level are presented.